2010
DOI: 10.1080/1067828x.2010.488960
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Prevalence and Attitudes Among Adults and Adolescents: Their Relation to Early Adolescent Alcohol Use in Rural Communities

Abstract: Although research has identified numerous neighborhood mechanisms influencing urban adolescent risk behaviors, less is known about how community contexts influence rural adolescents. This study explores perceived controls against adolescent drinking (i.e., tolerance of community adolescent alcohol use), adolescent perceptions of community supportiveness, and the prevalence of community alcohol use exhibited by adolescents and adults. Multilevel analyses were applied to 1,424 6th through 8th grade students resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…It is unclear why these patterns emerged in this way. It could be that rural substance use is driven more by overall permissive attitudes toward substance use (e.g., DeHaan & Boljevac, 2010; Gale et al, 2012; Lendardson et al, 2014; Maxwell et al, 2006; Meyer et al, 2008; VanGundy, 2006) which is fairly level over time, whereas urban substance use may be driven more by factors that change over time (e.g., peer pressure; e.g., CASA, 2011b; Sawyer & Stevenson, 2008). Future research should investigate how risk factors for substance use vary between rural and urban areas – it could be that there are different risk factors, or that these risk factors vary in prevalence between rural and urban.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why these patterns emerged in this way. It could be that rural substance use is driven more by overall permissive attitudes toward substance use (e.g., DeHaan & Boljevac, 2010; Gale et al, 2012; Lendardson et al, 2014; Maxwell et al, 2006; Meyer et al, 2008; VanGundy, 2006) which is fairly level over time, whereas urban substance use may be driven more by factors that change over time (e.g., peer pressure; e.g., CASA, 2011b; Sawyer & Stevenson, 2008). Future research should investigate how risk factors for substance use vary between rural and urban areas – it could be that there are different risk factors, or that these risk factors vary in prevalence between rural and urban.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found no associations with alcohol use (Aslund and Nilsson, 2013; De Haan, 2010; Ennett et al, 2008; Fulkerson et al, 2008; Maimon and Browning, 2012), whereas others found greater perceived neighborhood disorganization was longitudinally associated with a composite measure of ATOD use among 521 African American youth (Lambert et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…One review (Jackson et al, 2014) found only three studies that analyzed the impact of community attitudes regarding substance use on adolescent drinking, three studies assessing collective efficacy (i.e., social cohesion and efforts to informally control crime or deviance; see Sampson et al, 1997), and five studies examining social capital or neighborhood attachment. Most of these studies indicated null or contradictory effects of social processes on adolescent drug use (e.g., De Haan and Boljevac, 2010; Ennett et al, 2008, 2010; Musick et al, 2008). …”
Section: Introductionmentioning
confidence: 99%